Thiosemicarbazone p-Substituted Acetophenone Derivatives Promote the Loss of Mitochondrial Δψ, GSH Depletion, and Death in K562 Cells. (5th May 2015) - Pessoto, Felipe S.; Yokomizo, Cesar H.; Prieto, Tatiana; Fernandes, Cleverton S.; Silva, Alan P.; Kaiser, Carlos R.; Basso, Ernani A.; Nantes, Iseli L.
Abstract : A series of thiosemicarbazone (TSC) p -substituted acetophenone derivatives were synthesized and chemically characterized. The p -substituents appended to the phenyl group of the TSC structures were hydrogen, fluor, chlorine, methyl, and nitro, producing compounds named TSC-H, TSC-F, TSC-Cl, TSC-Me, and TSC-NO2, respectively. The TSC compounds were evaluated for their capacity to induce mitochondrial permeability, to deplete mitochondrial thiol content, and to promote cell death in the K562 cell lineage using flow cytometry and fluorescence microscopy. TSC-H, TSC-F, and TSC-Cl exhibited a bell-shaped dose-response curve for the induction of apoptosis in K562 cells due to the change from apoptosis to necrosis as the principal mechanism of cell death at the highest tested doses. TSC-Me and TSC-NO2 exhibited a typical dose-response profile, with a half maximal effective concentration of approximately 10  µ M for cell death. Cell death was also evaluated using the 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assay, which revealed lower toxicity of these compounds for peripheral blood mononuclear cells than for K562 cells. The possible mechanisms leading to cell death are discussed based on the observed effects of the new TSC compounds on the cellular thiol content and on mitochondrial bioenergetics.